2019
DOI: 10.1016/j.jhin.2019.02.012
|View full text |Cite
|
Sign up to set email alerts
|

In-vitro antibacterial and anti-encrustation performance of silver-polytetrafluoroethylene nanocomposite coated urinary catheters

Abstract: Background: Catheter-associated urinary tract infections (CAUTIs) are among the most common hospital-acquired infections, leading to increased morbidity and mortality. A major reason for this is that urinary catheters are not yet capable of preventing CAUTIs. Aim: To develop an anti-infective urinary catheter. Methods: An efficient silver-polytetrafluoroethylene (Ag-PTFE) nanocomposite coating was deposited on whole silicone catheters, and two in-vitro bladder models were designed to test antibacterial (agains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 31 publications
0
45
0
Order By: Relevance
“…Surface coatings ranging from antibacterial agents to natural glucosaminoglycans have previously been shown to reduce biofilm formation and encrustations with varying degrees of success. 5 However, to date, no study has assessed the potential encrustation properties of either uncoated Pellethane TPU or Pellethane TPU with an encrustation-resistant surface coating.…”
Section: Introductionmentioning
confidence: 99%
“…Surface coatings ranging from antibacterial agents to natural glucosaminoglycans have previously been shown to reduce biofilm formation and encrustations with varying degrees of success. 5 However, to date, no study has assessed the potential encrustation properties of either uncoated Pellethane TPU or Pellethane TPU with an encrustation-resistant surface coating.…”
Section: Introductionmentioning
confidence: 99%
“…For catheter coating research, catheter materials can have antifouling properties themselves and/or serve as a scaffold for impregnation or attachment of biocidal molecules. There are several anti-fouling catheters including those coated with hydrogels (most popular) [27,28], poly(tetrafluoroethylene) [34][35][36][37][38], polyzwitterions [39][40][41], and poly(ethylene glycol) [42][43][44][45][46]. Furthermore, surface topography modification [47][48][49][50] and enzymes-immobilized coatings [51][52][53][54][55][56][57][58] have been explored for prevention of microbial colonization and biofilm formation.…”
Section: Approaches To Restriction Of Cauti By Inhibition Of Microbiamentioning
confidence: 99%
“…PTFE-coated catheters, also known as Teflon-coated catheters, are commercially available from Bard Medical. Teflon has excellent non-stick properties via a low coefficient of friction, making it an optimal candidate for resisting bacterial colonization [34]; however, despite their desirable properties clinical data have shown that other coatings are better at preventing blockage and biofilm formation. For example, a clinical trial looking at the difference in blockage between (1) commercially available silicone, (2) silicone-coated, (3) teflon-coated, and (4) latex catheters that were placed for 14 days showed the silicone catheter had significantly lower blockage over latex and teflon-coated catheters [35].…”
Section: Poly(tetralfouroethalene) (Ptfe) Coatingmentioning
confidence: 99%
See 1 more Smart Citation
“…Overtime, the interaction between biofilm and urine leads to mineral precipitation around the catheters that may cause blockage of the inner lumen and demand medical attentions (Donlan, 2001;Wang et al, 2019). Eradication of biofilm after its formation is practically impossible to achieve due to increased risk of polymicrobial infection and the multiplied population's resistance to antibiotics (Singha et al, 2017).…”
Section: Missirlismentioning
confidence: 99%